(3QSGdI GdeYGfis - (3GdMcje gQeS , gQeS GdgQGeSIs
(3ChdgG (B:s
(3GdMceI ai eYGJHI GdfaS hQLhYgG Yf GdCehQ GdSadjI hMVgG Ydi GjdGFegG s
(3BNQgG (B:s
(3hbdHc ef GdYde eY GdYed GfaY ef cKjQ ef GdYde eY bdI GdYed s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdNGeSIs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQGdcJH GdeUQjI (B((3CNdGb JjehQ (B290) s
Keywords: (3GdadSaI hGdefWbs